Identifying pathways for managing multiple disturbances to limit plant invasions. Issue 4 (3rd June 2014) - Tanentzap, Andrew J.; Lee, William G.; Monks, Adrian; Ladley, Kate; Johnson, Peter N.; Rogers, Geoffrey M.; Comrie, Joy M.; Clarke, Dean A.; Hayman, Ella; Hooftman, Danny
Summary Plant invasions are predicted to accelerate in a world with increased anthropogenic disturbance. Non‐native species pre‐adapted to these disturbances may especially be poised to invade novel communities. Conservation managers therefore need predictions of how to alter disturbances to maximize the persistence of native biodiversity. We tested a multivariate hypothesis about the causal mechanisms underlying plant invasions in an ephemeral wetland in South Island, New Zealand, to inform management of this biodiverse but globally imperilled habitat. Our approach details among the first applications in ecology of Bayesian structural equation modelling, demonstrating its potential to inform management by disentangling the relative importance of strongly intercorrelated processes. We found that invasion by non‐native plants was lowest in sites where the physical disturbance caused by flooding was both intense and frequent. This effect was stronger than the positive response of non‐native species to high soil N supply, which was positively related to flooding. Sites flooded over a 4‐year period had greater reductions in invasion than those associated with floods in the year prior to plot measurement because non‐native species lacked traits for long‐term persistence beneath water. Grazer exclusion had a small positive effect on invasion, as non‐native species were preferentially selected by the herbivores at our site. Our results show that only species adapted to the dominant disturbance regimes at a site may become successful invaders. Species native to ephemeral wetlands have specially evolved traits that allow them to persist and dominate in these sites. Synthesis and applications. Predictions of invasions in a world of multiple disturbances clearly need to consider whether the evolutionary history of non‐native species predisposes them to invade novel communities. Maintaining hydrological and nutrient regimes of ephemeral wetlands will limit the number of introduced species that are pre‐adapted to become invasive.